PENGARUH INOKULUM CAMPURAN Lactobacillus plantarum DAN Saccharomyces cerevisiae TERHADAP KUALITAS ORGANOLEPTIK, FISIK, DAN KIMIA SILASE KULIT BUAH KAKAO - Muhammad Askari Zakariah; Ristanto Utomo; Zaenal Bacruddin (Buletin Peternakan, 2015)
This research was done to determine the effect of L. plantarum and S. cerevisiae innoculated into cocoa pod silage on organoleptic, physical and chemical quality. This experiment consist of four treatments namely silage of fresh harvested cocoa pods without inoculant as control (K); inoculated with L. plantarum (KLp); innoculated with S. cerevisiae (KSc); and innoculated with both L. plantarum and S. cerevisiae mixture (KLp+Sc) was cassava meal added as supplement. Each treatment was replicated 3 time. Ensilage was done for 21 days. Variables observed were properties of organoleptic (i.e. color, odor, texture and existence of fungal), physical (pH), and chemical (i.e. lactic acid content, content of dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), crude fiber (CF) and nitrogen free extract (NFE)). Collected data of organoleptic characteristic were analyzed by non-parametric test (Hedonic KruskalWallis), whereas physical and chemical data analyzed by one-way analysis of variance and followed by Duncan’s New Multiple Range Test for significant difference. Result showed the inoculum have effect (P<0.05) on characteristic of organoleptic (color and avaibility fungus) and chemical (dry matter, organic matter, extract ether, and nitrogen free extract content). Silage with inoculation Lp+Sc on silage significantly (P<0.05) had higher DM and OM concentration (22.66% vs 20.38% and 94.43% vs 93.72%), higher NFE (75.46% vs 70.51%) and lower EE (0.15% vs 0.87%, respectively), compared to control. Based on result, it can be concluded that silage with L. plantarum and S. cerevisiae mixture have better quality.(Key words: Cocoa pod, Lactobacillus plantarum, Saccharomyces cerevisiae, Silage)